Valence-band electronic structure and main optical properties of Cu2HgGeTe4: Theoretical simulation within a DFT framework and experimental XPS study. (June 2020) - Gabrelian, B.V.; Lavrentyev, A.A.; Vu, Tuan V.; Kalmykova, K.F.; Ananchenko, L.N.; Tkach, V.A.; Parasyuk, O.V.; Khyzhun, O.Y.
Highlights: Total and projected densities of states of Cu2 HgGeTe4 are computed within a DFT framework. Electronic structure of Cu2 HgGeTe4 alloy is studied experimentally by XPS. The DFT calculations fit well data of XPS measurements. Main optical constants of Cu2 HgGeTe4 are clarified by DFT calculations. Abstract: Comprehensive study from an experimental and theoretical viewpoint on the electronic structure and optical properties is made for quaternary telluride Cu2 HgGeTe4 . In particular, XPS spectra both core-level and within the valence band range, have been derived for Cu2 HgGeTe4 alloy. In addition, calculations of density of states (DOS) have been performed for the quaternary telluride within a density functional theory (DFT) framework and using exchange correlation potential in the form of modified Becke-Johnson (mBJ) functional and considering, in addition, Hubbard correction parameter U and the effect of spin-orbit (SO) coupling (mBJ + SO + U method). The mBJ + SO + U DFT calculations yield an excellent fit of total DOS curve to the XPS spectrum measured within the valence band range of the Cu2 HgGeTe4 alloy. Contributions to the valence band and conduction band regions from different electronic states of atoms composing Cu2 HgGeTe4 are discussed in detail in the present work and the main optical constants are calculated revealing a prospective of application of this compound in optoelectronic devices.